Preparation and characterization of Tribulus terrestris-loaded nanoparticles - M. Khanavi*; R. Dinarvand; M. Esfandiari-Manesh; N. Bagheri; A. Manayi; M. Mahmood Abadi (Iranian Society of Pharmacognosy, 2017)
Background and objectives: Tribulus terrestris is a flowering herb (Zygophyllaceae) with several properties in folk medicine such as diuretic, tonic, aphrodisiac, analgesic, astringent, and stomachic-lithotripter activities. Although, some extracts and phytochemicals represent excellent bio-activity in vitro, less or no in vivo activity is observed due to their improper molecular size. The intend of this research was investigation of the feasibility of encapsulating T. terrestris into [poly (lactic-co-glycolic acid)] PLGA nanoparticles. Methods: Aerial parts of the plant were extracted with aqueous ethanol 85% by percolation apparatus. The nanoparticles of T. terrestris-loaded were prepared using a modified simultaneous double-emulsion solvent evaporation/diffusion method. Elucidations were made on the basis of scanning electron microscopy (SEM) and differential scanning calorimetry (DSC). The content of nanoparticles was analyzed by HPLC with indirect method. Results: The results stated that increasing the portion of plant extract could cause bigger size with no considerable increase in polydispersity index (PDI). The encapsulation efficiency of T. terrestris-loaded nanoparticles was 40.3 to 78.5 and the drug loadings were 0.806 to 6.104, with different ratios of extract. The overall pattern of the release in SDS 1% in dialysis bag in all formulations showed similar and biphasic release kinetic, an initial burst release in the first day followed by constant release over 10 days. Conclusion: An effective approach for the preparation of T. terrestris-loaded PLGA nanoparticles was performed. The controlled release proﬁle showed that these biodegradable PLGA nanoparticles had great potential and should be given particular consideration in further biological researches.